PENGARUH LABEL HALAL, DUKUNGAN SELEBRITI, DAN ULASAN MELALUI MEDIA ELEKTRONIK TERHADAP MINAT BELI DENGAN CITRA MEREK SEBAGAI VARIABEL INTERVENING (Studi pada Produk Kosmetik Wardah di Kota Semarang) - Maulida, Laila; Dirgantara, I Made Bayu (Faculty of Economics and Business Diponegoro University, 2019)
This research aimed to analyse the effect of halal label, celebrity endorser, andelectronic word of mouth on purchase intention with brand image as the interveningvariable (a study on Wardah cosmetic products in Semarang city). The variables is used inthis study consisted of 3 independent variables such as halal label (X1), celebrity endorser(X2), and electronic word of mouth (X3), intervening variable is brand image (Y1), anddependent variable is purchase intention (Y2).The samples in this research are 160 respondents of women within age of 15-54years old who recognize Wardah brand, whether interested or not to buy Wardah cosmeticproducts in Semarang city. The sampling method used in this research is non-probabilitysampling method with purposive sampling technique. The method of data collection isconducted through questionnaires. This research uses analytical technique of StructuralEquation Model (SEM) with AMOS 22.0 as the analysis instrument.The results of this research show that halal label has a positive and significanteffect on brand image, celebrity endorser has a positive and significant effect on brandimage, electronic word of mouth has a positive and significant effect on brand image,electronic word of mouth has a positive and significant effect on purchase intention, andbrand image has a positive and significant effect on purchase intention.